(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article discusses dysphemisms, one of the lesser-studied areas in linguistics. Dysphemisms are considered a subsystem of the broader concept known as X-phemisms, and in some literature, they are also referred to as cacophemisms. In addition to discussing this, the article provides insights into the similarities and differences between euphemism and dysphemism, along with examples. It also includes information about the types of dysphemisms, the historical development process, starting from ancient scholars to contemporary Uzbek scholars who have worked in this field.